The effect of curcumin on embryonic in vitro development in experimental polycystic ovary syndrome: An experimental study - Yousef Nasiri Bari; Vahab Babapour; Abbas Ahmadi; Morteza Zendehdel Kheybari; Ghasem Akbari (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Polycystic ovary syndrome (PCOS) is a common disease in women. Some plant compounds which have antioxidant properties, such as curcumin, may be useful for these patients when delivered orally or in vitro. Objective: The aim of this study was to evaluate the impact of PCOS on oocyte quality and the effect of curcumin on in vitro fertilization of oocytes. Materials and Methods: In this experimental study, Naval Medical Research Institute mice aged six to eight wk were used. Mice were divided into five experimental groups (control, experimental PCOS, curcumin 6, 12 and 24 μM). To induce experimental PCOS, estradiol valerate (100 mg/kg, IP) was injected. The total antioxidant capacity and production of malondialdehyde in ovarian tissue and blood serum were evaluated in all groups. Finally, 6, 12 and 24 μM of curcumin were added to the culture medium of the PCOS group oocytes and development in the different groups was evaluated. Results: A high percentage of oocytes for fertilization were not in good condition in terms of number and quality in the group of PCOS. The addition of curcumin to the embryo culture medium was associated with a higher percentage of fertilized oocytes, two-cells and blastocysts. This increase was significant at a concentration of 24 μM (p ≤ 0.01). Conclusion: Given that adding curcumin seemed to improve fetal growth and prevent the harmful effects of oxygen free radicals on the culture medium, it is recommended to add a certain concentration of curcumin under normal conditions without oxidative stress.